Psycholinguistic Bases of Speech Adaptation by Children of Immigrants - Tarasiuk, Inna (East European Journal of Psycholinguistics, 2014)
The article focuses on the issue of speech adaptation of immigrant children to a foreign environment. Speech adaptation is defined by the author through the main psycholinguistic features and functions of both constituents - adaptation and speech. The concept is viewed as the effective use of all language means available in linguocultural environment for realizing individual needs, motives, and obtaining new values. It was found out that in the course of speech adaptation, immigrants were strengthening their cognitive abilities, developing volition, while manifesting personal growth and self-realization. Because of its individual nature, speech adaptation is not limited by age, temporal features, and area of inhabitancy. The empirical study results clearly show the influence of gender, school type, and psychoemotional states of immigrant children on their successful speech adaptation. Furthermore, a psycho-didactic training program aimed at developing speech adaptation by immigrant children was designed. The results of a psycholinguistic experiment held with control and experimental groups show the efficacy of the introduced psycho-didactic training program that facilitates immigrant childrens’ speech adaptation. References Blynova, O. (2010). Psykholohichni osnovy sotsialnoi mobilnosti osobystosti [Psychological bases of social mobility by personality]. Kherson: Kherson State University. Bokus, B. (2004). Inter-mind phenomena in child narrative discourse. Pragmatics, 14(4), 391–408. Dukarevych, M. (1990). Yanshyn, P. (1990). Rysunok nesushchestvuiushcheho zhyvotnoho [The picture of nonexistent animal]. Practical Methods of Psychodiagnostic. Psychodiagnostic of Motivation by Self regulation, 54–73. Horoshko, Ye. (2001). Intehratyvnaia Model Svobodnoho Assotsyatyvnoho Eksperymenta [Integration Model of Free Associative Test]. Kharkiv: Ra-Karavella. Kalmykova, L. (2008). Psykholohichni zasady rozriznennia operatsii i dii yak odynyts movlennievoi diialnosti [Psychological bases of differences in operation and action as parts of speech activity]. Humanitarian Bulletin of Hryhoriy Skovoroda Pereyaslav-Khmelnytskyi State Pedagogical University, 15, 86–88. Korniiaka, O. (2006). Psykholohiia Komunikatyvnoyi Kultury Shkoliara [Psychology of Students’ Communicative Culture]. Kyiv: Millenium. Kovalchuk, I. (2008). Psykholinhvistychni kontseptsii navchannia inozemnykh mov [Psycholinguistic concept of foreign language teaching]. Naukovi Zapysky of Ostroh Academy, 9. Lavrynenko, O. (2011). Strukturno - funktsionalni osoblyvosti movnoi osobystosti studentiv [Structure-functional features of language personality of students]. Unpublished Ph. D. thesis. Lutsk: Lesya Ukrainka Volyn National University. Lebedeva, N. (1993). Sotsyalnaya Psykhologiya Etnycheskikh Migratsy [Social Psychology of Ethnic Migration]. Moscow: Yeya. Leontyev, A. (2001). Yazyk y rechevaia deiatelnost v obshchei y pedahohycheskoi psykholohyy [Language and Speech Activity in General and Pedagogical Psychology]. Voronezh: Modek. Lüscher M. (2003). Das Harmoniegesetz in Uns. Ullstein. Lüscher M. (2005). Der 4-Farben-Mensch: Der Weg Zum Inneren Gleichgewicht. Ullstein. Chepelieva, N., Smulson, M., Shylovska O. & Hutsol, S. (2007). Naratyvni Psykhotekhnolohii [Narrative Psychotechnologies]. Kyiv: Hlavnyk. Orap, M. (2007). Movlennieva diialnist u protsesi samopiznannia osobystosti [Speech actions during self cognition by personality]. Humanitarian Bulletin of Hryhoriy Skovoroda Pereyaslav-Khmelnytskyi State Pedagogical University, 200–203. Orban-Lembryk, L., Podhuretski, Yu. (2008). Psykholohichni Zasady Spilkuvannia [Psychological Bases of Communication]. Ivano-Frankivsk: Nova Zoria. Romanova, E. (2001). Hrafycheskyie Metody v Praktycheskoi Psykhologii [Graphic Methods in Applied Psychology]. St. Petersburg: Rech. Serkin, V. (2008). Metody Psykholohyy y Subyektivnoi Semantyky y Psykhosemantyky [Methods of Psychology in Subject Semantics and Psychosemantics]. Moscow: Pchela. Shyriayeva, T. (2009). Psykholinhvistychni zasoby rozvytku piznavalnoi sfery studentiv v umovakh ovolodinnia inozemnoiu movoiu [Psychological means of development sphere of students during learning a foreign language]. Unpublished Ph.D. thesis. Khmelnytskyi: Bohdan Khmelnytsyi National Academy of State Border Service. Solovey, O. (2010). Psykholohichni osoblyvosti movlennievoi diialnosti ditei z hiperaktyvnym rozladom ta defitsytom uvahy [Psychological features of speech actions by children with hyperactive disorder]. Unpublished Ph.D. thesis. Lutsk: Lesya Ukrainka Volyn National University. Sukhomlynskyi, V. (1976). Sertse Viddaiu Ditiam [Giving My Heart to Children]. Kyiv: Rad. Shkola. Tarasiuk, I. (2013). Psykholohichni osoblyvosti funktsionalnykh proiaviv movlennievoi adaptatsii ditei mihrantiv [Psychological features of functional manifestation of immigrant children’s speech adaptation]. Psychological Prospects Journal, 21, 229–238. Venher, A. (2005). Psykhodyahnostycheskye Rysunochnyie Testy: Illiustryrovannoe Rukovodstvo [Psychodiagnostic Drawing Tests: Illustrated Guide]. Moscow: Vlados-Press. Volobuyeva, O. (2011). Psykholohichni osoblyvosti formuvannia kompetentsii v chytanni inozemnoiu movoiu maibutnikh ofitseriv-prykordonnykiv [Psychological features of forming of competence in reading in foreign language by future officer-frontier guards]. Psychological Journal of Bohdan Khmelnytsyi National Academy of State Border Service, 57, 104–110. Vygotsky, L. (1991). Voobrazhenye i Tvorchestvo v Detskom Vozraste. Psykholohycheskyi Ocherk: Kniga dlia Uchytelia [The Imagination and Creativity in Child Age. Psychological Book for Teacher]. Moscow: Prosveshchenye. Zasiekina, L., Zasiekin, S. (2008). Psykholinhvistychna Diahnostyka [Psycholinguistic Diagnostic]. Lutsk: Vezha. Zavatska, N. (2011). Osoblyvosti funktsionuvannia intrapersonalnykh skladovykh adaptatsiinoho potentsialu osobystosti v kryzovi periody zhyttia [The features of functioning of intrapersonal constituents of adaptation potential by the personality in crisis periods of life]. Journal of Theoretical and Practical Problems of Psychology, 2(26), 12–19. Zimniaya, I. (2001). Lynhvopsykholohyia Rechevoi Deiatelnosty [Linguopsychology of Speech Activity]. Voronezh: Modek.